Metode Pembelajaran Pendidikan Agama Kristen di Era Digital: Tantangan dan Peluang bagi Guru PAK - Rianto Timu Tirinna (International Forum of Researchers and Lecturers, 2026)
This study aims to examine relevant and effective Christian Religious Education (CRE) learning methods in the digital era. The rapid development of information and communication technology has brought significant changes in education, including CRE instruction. The research method employed is a literature study with a descriptive-analytical approach to various academic sources and technology-based CRE learning practices. The results indicate that integrating digital media such as online learning platforms, Bible-based interactive applications, and social media creatively can enhance students' engagement and understanding of Christian faith values. Furthermore, the use of digital technology opens wider opportunities for contextual and meaningful faith formation across diverse learning environments. The study also identifies key challenges faced by CRE teachers, namely digital readiness, infrastructure limitations, and maintaining relational and spiritual dimensions in virtual learning environments. Teachers must therefore be equipped not only technologically but also theologically to navigate these complexities. The research concludes that the transformation of CRE methods in the digital era is not merely a technology adoption but a holistic theological integration of faith, technology, and pedagogy.